COMPARATIVE ANALYSIS OF ADJECTIVES IN ENGLISH AND UZBEK LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: this article explores the characteristics of adjectives in both English and Uzbek languages. It discusses the similarities and differences in terms of their morphological features, syntactic functions, and semantic properties. The analysis sheds light on how adjectives are formed, how they are used in sentences, and how they convey meaning in different contexts. The comparative approach allows readers to understand the unique aspects of adjectives in each language while highlighting the potential challenges for learners of English or Uzbek as a second language.